Outcomes of Palliative Radiotherapy in Metastatic Epidural Spinal Cord Compression in Lung Cancer—A Prospective Observational Study from Tata Memorial Hospital - Tibdewal, Anil; Sharma, Alisha; Gurram, Lavanya; Mummudi, Naveen; Agarwal, Jaiprakash (South Asian Journal of Cancer, 2021)
Background Metastatic epidural spinal cord compression (MESCC) secondary to lung cancer (LC) is a debilitating complication associated with poor prognosis and is commonly treated with radiotherapy (RT). There is no consensus for RT dose fractionation in spinal cord compression.Methods Forty consecutive patients of LC with radiological evidence of MESCC treated with palliative RT were evaluated for functional outcomes (pain, ambulation, and sphincter function) at 2-, 4-, and 24-week post RT completion. Pain assessment was done using visual analogue scale (VAS) and response was categorized according to international consensus criteria, ambulation status (AS) using Tomita’s scale, and sphincter function by the presence or absence of a catheter. Overall survival (OS) was assessed using Kaplan-Meier method and compared using log-rank test. Impact of potential prognostic factors on survival was also analyzed and p-value ≤0.05 was considered significant.Results Sixteen, 22, and two patients received 8 Gy single fraction (SF), 20 Gy in five fractions (20/5), and 30 Gy in 10 fractions (30/10), respectively. At 2 weeks, overall response (OR) rates of pain, ambulation, and sphincter control were 73, 81, and 81%, respectively. At 4 and 24 weeks, 93.7, 84.3, 87.5% and 88, 94, 76.5% had OR, respectively. Median OS was 4 months. Six- and 12-months OS was 50 and 37.5%. Nonsignificant difference in OS was seen between SF and 20/5 fractions (median 2.2 vs. 7.1 months, p = 0.39). Age ≤50 years was the only significant factor (p <0.05) in univariate analysis for OS.Conclusion Radiotherapy provided equivalent pain control, ambulation, and sphincter function compared with reported literature in MESCC. Nonsignificant difference in OS exists between SF and multifraction RT regimens.
Keywords: cord compression; radiotherapy; lung cancer; ambulation